Comparison of growth inhibition profiles and mechanisms of apoptosis induction in human colon cancer cell lines by isothiocyanates and indoles from Brassicaceae - Pappa, Gerlinde; Lichtenberg, Maike; Bartsch, Helmut; Gerhäuser, Clarissa (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2006)
The isothiocyanates sulforaphane and PEITC (β-phenethyl isothiocyanate) as well as the indoles indole-3-carbinol and its condensation product 3,3′-diindolylmethane are known to inhibit cancer cell proliferation and induce apoptosis. In this study, we compared the cell growth inhibitory potential of the four compounds on the p53 wild type human colon cancer cell line 40-16 (p53+/+) and its p53 knockout derivative 379.2 (p53−/−) (both derived from HCT116). Using sulforhodamin B staining to assess cell proliferation, we found that the isothiocyanates were strongly cytotoxic, whereas the indoles inhibited cell growth in a cytostatic manner. Half-maximal inhibitory concentrations of all four compounds in both cell lines ranged from 5-15μM after 24, 48 and 72h of treatment. Apoptosis induction was analyzed by immunoblotting of poly(ADP-ribose)polymerase (PARP). Treatment with sulforaphane (15μM), PEITC (10μM), indole-3-carbinol (10μM) and 3,3′-diindolylmethane (10μM) induced PARP cleavage after 24 and 48h in both 40-16 and the 379.2 cell lines, suggestive of a p53-independent mechanism of apoptosis induction. In cultured 40-16 cells, activation of caspase-9 and -7 detected by Western blotting indicated involvement of the mitochondrial pathway. We detected time- and concentration-dependent changes in protein expression of anti-apoptotic Bcl-xL as well as pro-apoptotic Bax and Bak proteins. Of note is that for sulforaphane only, ratios of pro- to anti-apoptotic Bcl-2 family protein levels directly correlated with apoptosis induction measured by PARP cleavage. Taken together, we demonstrated that the glucosinolate breakdown products investigated in this study have distinct profiles of cell growth inhibition, potential to induce p53-independent apoptosis and to modulate Bcl-2 family protein expression in human colon cancer cell lines.
Gesehen am 23.11.2020